2014
DOI: 10.3945/ajcn.113.079152
|View full text |Cite
|
Sign up to set email alerts
|

Nut consumption in relation to cardiovascular disease risk and type 2 diabetes: a systematic review and meta-analysis of prospective studies

Abstract: A higher consumption of nuts was associated with reduced risk of CAD and hypertension but not stroke or T2D. Large randomized controlled trials are warranted to confirm the observed associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 39 publications
10
79
0
2
Order By: Relevance
“…In the Framingham Study, an inverse association was observed between fruit and vegetable intake and development of stoke in middle-aged men after 20 years of follow-up [40]. Likewise, consumption of nuts was significantly inversely associated with hypertension (RR: 0.66; 95% CI: 0.44, 1.00; P = 0.049) in a recent meta-analysis of four prospective studies [12]. Dietary patterns such as the DASH diet [19], the Mediterranean diet [21] and the Nordic diet [41] have been shown to reduce BP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Framingham Study, an inverse association was observed between fruit and vegetable intake and development of stoke in middle-aged men after 20 years of follow-up [40]. Likewise, consumption of nuts was significantly inversely associated with hypertension (RR: 0.66; 95% CI: 0.44, 1.00; P = 0.049) in a recent meta-analysis of four prospective studies [12]. Dietary patterns such as the DASH diet [19], the Mediterranean diet [21] and the Nordic diet [41] have been shown to reduce BP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effect of individual foods on BP has been investigated in randomized controlled trials and observational studies but with conflicting results. Foods investigated include fruit and vegetables [9], dairy foods [10], eggs [11], nuts [12], pulses [13], meat [14], tea [15] and coffee [16].…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of nuts in the reduction of the cardiovascular disease risk was acknowledged by the two meta-analyses, which found that the consumption of them in the amount of on serving a week is related to the decrease in risk by 5% [30,31]. On the other hand Zhou et al [31] showed that the daily consumption of nuts enhances the effect up to 19%. According to the FFQ analysis (Food Frequency Questionnaire) [32], conducted in years 1980-2002 in women with type 2 diabetes (6309 subjects), the consumption of at least 5 servings per week was associated with lower probability of developing CVD by 44% in comparison to the control group.…”
Section: The Significance Of Nuts In the Cardiovascular Disease Risk mentioning
confidence: 98%
“…In connection with the foregoing it is extremely important to monitor dyslipidemia, hypertension as well as overweight and obesity, as additional factors affecting the risk of CVD (cardiovascular diseases) in patients with type 2 diabetes [3,4]. The contribution of nuts in the reduction of the cardiovascular disease risk was acknowledged by the two meta-analyses, which found that the consumption of them in the amount of on serving a week is related to the decrease in risk by 5% [30,31]. On the other hand Zhou et al [31] showed that the daily consumption of nuts enhances the effect up to 19%.…”
Section: The Significance Of Nuts In the Cardiovascular Disease Risk mentioning
confidence: 99%
See 1 more Smart Citation